Immunoprofile of α‐Gal‐ and B‐antigen‐specific responses differentiates red meat‐allergic patients from healthy individuals. Issue 7 (5th February 2018) - Apostolovic, D.; Rodrigues, R.; Thomas, P.; Starkhammar, M.; Hamsten, C.; van Hage, M.
Abstract: Background: The galactose‐α‐1, 3‐galactose (α‐Gal) epitope is involved in red meat allergy. As α‐Gal is structurally similar to the blood group B‐antigen, we explored the relationship between the immune responses to α‐Gal‐ and the B‐antigen in red meat‐allergic patients compared to healthy A/O or B blood donors. Methods: Sera from 51 red meat‐allergic patients IgE‐positive to α‐Gal and 102 healthy blood donors (51 blood group A/O; 51 blood group B) were included. α‐Gal‐ and B‐antigen‐specific IgE (ImmunoCAP) and IgG/IgG1‐4 (ELISA) responses were determined. Basophil activation tests were performed. Results: Fifteen healthy donors were IgE positive to α‐Gal, of which 3 had blood group B. The allergic patients had significantly higher α‐Gal IgE levels compared to the healthy donors. The majority of the allergic patients, but none of the healthy donors, had IgE against the B‐antigen. Inhibition studies revealed cross‐reactivity between α‐Gal and the B‐antigen. The biological activity of the B‐antigen was confirmed by basophil activation tests. Anti‐α‐Gal IgG1 and IgG4 levels were significantly higher in the patients compared to the healthy donors. Moreover, the IgG response to the B‐antigen was comparable between the allergic patients and healthy A/O donors. Conclusion: Red meat‐allergic patients showed significantly higher α‐Gal IgE, IgG1, and IgG4 levels, reflecting a Th2 response, compared to healthy blood donors. Blood group B donors had significantly reduced antibody responses to α‐Gal, due to similarities with the B‐antigen, resulting in a lower risk of sensitization to α‐Gal and development of red meat allergy.